Adding new “C”s to our lexicon when considering the future of comparative education research: Complexity, care, and caution - Sider, Steve (Revista Española de Educación Comparada, 2021)
This article explores the question “What can inclusive comparative and international education research look like?” I situate my own experience in comparative research to consider three “Cs” for the future of comparative and international education: Complexity, care, and cautions. Complexity refers to the divisive and challenging global issues that exist and in which comparative education research takes place. As comparative and international education researchers, we need to practice an ethic of care in engaging in research in increasingly complex times. I conclude by providing three cautions for the future of research: transparency, positionality, and ethical relationality.